2005
DOI: 10.1002/dei.20
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics and deaf children: an exploration of barriers to success

Abstract: Consistent evidence from research studies between 1980 and 2000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…This is evident from the mean scores provided in Table 5. Similar observations were made in earlier studies by Pau (1995) and Wood et al, (1983), Nunes and Moreno (2002), Swanwick et al (2005). They too observed that children with hearing impairment performed poorer than typically developing children on the tasks evaluated by them.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is evident from the mean scores provided in Table 5. Similar observations were made in earlier studies by Pau (1995) and Wood et al, (1983), Nunes and Moreno (2002), Swanwick et al (2005). They too observed that children with hearing impairment performed poorer than typically developing children on the tasks evaluated by them.…”
Section: Discussionsupporting
confidence: 89%
“…Similar observations were made by Meadow-Orlans (1980). Swanwick et al (2005) reported that findings from research studies between 1980 -2000 suggest that there is an average delay of 2 to 3.5 years in mathematical achievement in children with hearing loss. However, many of these children were reported to show similar processes as their hearing peers, confirming the suggestion of delay in mathematical development rather than a disorder or deviant development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the researches on whether there are gender differences in mathematical performance of hearing individuals are still controversial, so we want to explore the gender differences in numerical magnitude processing and arithmetic computation of deaf adolescents. Thirdly, in view of the importance of mathematical ability and the lag of deaf children in arithmetic (Traxler, 2000 ; Swanwick et al, 2005 ; Gottardis et al, 2011 ), against the background of the found associations between numerical magnitude processing and arithmetical ability of hearing individuals (Fazio et al, 2014 ; Zhang et al, 2016 ; Schneider et al, 2017 ) and no significant differences between deaf and hearing individuals in their number representation processes (Zarfaty et al, 2004 ; Arfé et al, 2011 ; Barbosa, 2013 ), we also aimed to examine whether numerical magnitude processing (symbolic, non-symbolic) is a predictor of the arithmetical ability of the deaf adolescents.…”
Section: Introductionmentioning
confidence: 99%